Analysis Vehicle TWC Light-off Characteristics on AMESim Platform - Zhuang Wen Wu (Institute of Advanced Engineering and Science, 2013)
Though building an AMESim physical model of vehicle three-way catalytic converter (TWC), this article aims to study the light-off characteristics of TWC. By solving the energy and mass conservation equations of gas-solid two phase of the model, this article obtains the emissions conversion rate, such as CO, unburned hydrocarbons (CaHb) and nitrogen oxides (NOx) under different parameters. The results show that, the TWC light-off characteristics can be affected by the engine control strategy, allocation of TWC and the structure of TWC carrier.DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.1476